MODERN EDUCATIONAL TECHNOLOGIES IN TEACHING ENGLISH (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The landscape of English language instruction has undergone profound transformation through modern educational technologies. These advancements have not only redefined classroom environments and pedagogical strategies but have also expanded opportunities for individualized learning, global communication, and creative engagement in language practice. As emerging digital tools, platforms, and resources continue to accelerate, educators face new possibilities and challenges in adapting their teaching methods accordingly. This article thoroughly explores how modern educational technologies are reshaping the teaching and learning of English, analyzing their pedagogical implications, the benefits they offer, and the obstacles they present. By integrating theoretical perspectives and practical examples, the article demonstrates the powerful potential of technology to foster motivation, collaboration, autonomy, and communicative competence in English language education. The conclusion synthesizes key insights and proposes recommendations for effectively leveraging educational technology in modern classrooms.
Keywords: English language teaching, educational technologies, digital learning, language instruction, innovation in education, ICT, e-learning, motivation, learner autonomy.